Peningkatan Daya Saing Usaha Peternakan Hewan Qurban Melalui Pelatihan Studi Kelayakan Bisnis Syariah di CV. Arba Madani (Unit Usaha Arba Farm) - El Hasan, Sawqi Saad; Harsanto, Molbi Febrio; Wijandari, Ana (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2024)
This Community Service Activity examines the goat farming business at CV. Arba Madani, specifically at the Arba Farm Unit located in Cibening Village, Pamijahan District, Bogor Regency, West Java Province. The primary objective of the training is to enhance participants' knowledge and skills in analyzing the business feasibility of goat and sheep farming. The methodology employed is a combination of lectures and hands-on practice, conducted in three stages: preparation, implementation and evaluation. The results of this service activity include the development of an entrepreneurial mindset, knowledge of business feasibility analysis, the application of intensive goat husbandry practices, and the enhancement of the economic value of the business. This activity is expected to have a positive impact on the competitiveness of the qurban livestock farming business and to promote local economic development through the improvement of skills and knowledge among the entrepreneurs at CV. Arba Madani.